Answer:
Explanation:
From the condition of perpendicularity, for two lines to be perpendicular to each other the product of their gradients must equal to ( -1 ).
Same time, equation of a straight line is ; y = mx+ c where m us the gradient and c is the point of intersection of the line on y axis. Therefore, the gradient of this equation m1 ,= -5 and the gradient m2 of the second line will be 1/5. Therefore, the equation of the second line perpendicular to
y = -5x + 6 ; y = x/5 + 6 .
Therefore, y = x/5 + 6 is the new equation.